Small GTPase Rab5 participates in chromosome congression and regulates localization of the centromere-associated protein CENP-F to kinetochores - Serio, Gaetana (National Academy of Sciences, 2011)
Rab5 is a small GTPase known to regulate vesicular trafficking during interphase. Here, we show that Rab5 also plays an unexpected role during mitotic progression. RNAi-mediated silencing of Rab5 caused defects in chromosome congression and extensive prometaphase delay, and it correlated with a severe reduction in the localization of the centromere-associated protein CENP-F to kinetochores. CENP-F is a component of the nuclear matrix required for chromosome congression that, at mitotic entry, localizes to the nuclear envelope and assembles on kinetochores, contributing to the establishment of kinetochore microtubule interactions. We found that Rab5 forms a complex with a subset of CENP-F in mitotic cells and regulates the kinetics of release of CENP-F from the nuclear envelope and its accumulation on kinetochores. Simultaneous depletion of both Rab5 and CENP-F recapitulated the mitotic defects caused by silencing of either Rab5 or CENP-F alone, indicating epistatic roles for these two proteins in the pathway that orchestrates chromosome congression. These results reveal the involvement of Rab5 in the proper execution of mitotic programs whose deregulation can undermine chromosomal stability.